Manipulating the interaction of Pt NPs with N-hollow carbon spheres by F-doping for boosting oxygen reduction/methanol oxidation reactions. Issue 8 (7th February 2023) - Lyu, Chaojie; Cheng, Jiarun; Yang, Yuquan; Wu, Jiwen; Wu, Kaili; Yang, Yunguo; Lau, Woon-Ming; Wang, Ning; Pang, Dawei; Zheng, Jinlong
Abstract : F-doping enhances the strong interaction between Pt NPs and carbon skeleton, and leads to higher Pt x + content that can effectively adsorb *OOH intermediates for direct 4e − pathway in ORR, also promote the complete oxidation of COads to CO2 in MOR. Abstract : Highly dispersed Pt NPs anchored in hierarchically N, F co-doped hollow carbon spheres (Pt@N, F-HCS) were synthesized through a template-assisted strategy followed by fluorination and wet chemical reduction. Due to the introduction of F heteroatoms into the carbon skeleton, the degree of d–π electron conjugation between Pt NPs and N, F-HCS can be enhanced. This will lead to higher Pt x + content in Pt species, which is beneficial for the effective adsorption of *OOH intermediates and is conducive to O–O bond breaking and triggers the direct 4-electron transfer mechanism for the ORR. In particular, the onset potential and half-wave potential values for the ORR are more positive than Pt@N-HCS without F doping, even outperforming 20%Pt/C. Besides, the Pt@N, F-HCS catalyst also possesses the smallest onset potential and largest methanol oxidation current for the MOR. In alkaline media, abundant OH − will be adsorbed around the Pt x + sites due to its higher positive valence, and the reaction intermediate COads generated in Pt x + sites will be further oxidized to the final product, CO2, thus improving the MOR activity and CO tolerance capacity. This heteroatom-doping strategy is favorable for enhancing the interaction between Pt NPs and the carbon-based support, and also provides insight to promote the activity and selectivity for direct methanol fuel cells.